1993
DOI: 10.1128/mcb.13.12.7652
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, and cDNA cloning of an AU-rich element RNA-binding protein, AUF1.

Abstract: The degradation of some proto-oncogene and lymphokine mRNAs is controlled in part by an AU-rich element (ARE) in the 3' untranslated region. It was shown previously (G. Brewer, Mol. Cell. Biol. 11:2460-2466) that two polypeptides (37 and 40 kDa) copurified with fractions of a 130,000 x g postribosomal supernatant (S130) from K562 cells that selectively accelerated degradation of c-myc mRNA in a cell-free decay system. These polypeptides bound specifically to the c-myc and granulocyte-macrophage colony-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
483
4
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 506 publications
(500 citation statements)
references
References 75 publications
12
483
4
1
Order By: Relevance
“…(a) silver staining. (b) ECL detection after incubation with anti-AUF1 antibodies AUF1, HuR and c-myc mRNA expression in vivo I Lafon et al 1995; Zhang et al, 1993) revealed two in frame insertions, one 57 bp long in the 5' coding region and another, 147 bp long, in the 3' coding region ( Figure 3A). These variations, which result from alternative pre-mRNA splicing (Wagner et al, 1998), lead either to a 19 amino-acid (19-aa) insertion in the N-terminal portion of RRM1 or to a 49-amino acid (49-aa) insertion in the C-terminal region of the AUF1 isoforms, respectively (see Figure 3A).…”
Section: Complexity Of Auf1 Mrnasmentioning
confidence: 97%
See 4 more Smart Citations
“…(a) silver staining. (b) ECL detection after incubation with anti-AUF1 antibodies AUF1, HuR and c-myc mRNA expression in vivo I Lafon et al 1995; Zhang et al, 1993) revealed two in frame insertions, one 57 bp long in the 5' coding region and another, 147 bp long, in the 3' coding region ( Figure 3A). These variations, which result from alternative pre-mRNA splicing (Wagner et al, 1998), lead either to a 19 amino-acid (19-aa) insertion in the N-terminal portion of RRM1 or to a 49-amino acid (49-aa) insertion in the C-terminal region of the AUF1 isoforms, respectively (see Figure 3A).…”
Section: Complexity Of Auf1 Mrnasmentioning
confidence: 97%
“…The AUF1 antibodies used in the Western blot assay initially revealed three immunologically related polypeptides of 37 (p37), 40 (p40) and 45 (p45) kDa in extracts from the human K562 cell line (Zhang et al, 1993). These three polypeptides are also observed in murine tissues, though their relative abundance is not identical.…”
Section: Auf1 Protein Expressionmentioning
confidence: 99%
See 3 more Smart Citations